A preliminary investigation of the effects of short‐duration, vigorous exercise following sleep restriction, fragmentation and extension on appetite and mood in inactive, middle‐aged men. (27th October 2020) - Larsen, Penelope; Marino, Frank E.; Guelfi, Kym; Duffield, Rob; Skein, Melissa
Abstract: This preliminary study aimed to investigate the effect of exercise on appetite and mood following multiple days of sleep disruption (restriction [RES], fragmentation [FRAG]) or sleep extension (EXT), compared to normal sleep (CONT) in inactive, middle‐aged men. Nine men completed four randomised trials initiated by 3 nights (day 1–3) of CONT (6.5–8 hr), RES (4 hr), FRAG (6.5–8 hr, interrupted at 2‐hr intervals) or EXT (10 hr). On day 4 between 08:30 and 11:00 hours, perceived appetite, food cravings, appetite‐related hormones (acylated ghrelin, leptin, peptide tyrosine–tyrosine [PYY]total ), glucose, mood states and wellness (stress, fatigue, soreness, and mood) were assessed before (post‐sleep manipulation [SM]) and after (post‐exercise [EX]) a 20‐min vigorous cycling bout (rating of perceived exertion: 15). There was no effect of sleep manipulation or exercise on perceived appetite ( p = .34–.62). Some aspects of food craving were altered after RES and EXT, with vigorous exercise attenuating the desire for sweet foods in RES ( p = .12). PYYtotal was lower after RES compared to EXT and FRAG ( p = .03), but was unaltered by exercise ( p = .03). Ghrelin was higher for RES and EXT compared to CONT and FRAG after exercise ( p = .001–.03). Total wellness was reduced and total mood disturbance (TMD) was higher after RES and FRAG compared to CONT and EXT ( p ≤ .05). However, vigorous exercise countered these changes, with wellness and TMD remaining significantly impaired for FRAG compared to EXT only at this time ( p = .02–.03). Vigorous exercise mitigates some aspects of food cravings and counters the impaired mood states that exist after multiple days of restricted and fragmented sleep.